Voice disorders in mucosal leishmaniasis. - Ana Cristina Nunes Ruas; Márcia Mendonça Lucena; Ananda Dutra da Costa; Jéssica Rafael Vieira; Maria Helena de Araújo-Melo; Benivaldo Ramos Ferreira Terceiro; Tania Salgado de Sousa Torraca; Armando de Oliveira Schubach; Claudia Maria Valete-Rosalino (PLoS ONE, 2014)
INTRODUCTION: Leishmaniasis is considered as one of the six most important infectious diseases because of its high detection coefficient and ability to produce deformities. In most cases, mucosal leishmaniasis (ML) occurs as a consequence of cutaneous leishmaniasis. If left untreated, mucosal lesions can leave sequelae, interfering in the swallowing, breathing, voice and speech processes and requiring rehabilitation. OBJECTIVE: To describe the anatomical characteristics and voice quality of ML patients. MATERIALS AND METHODS: A descriptive transversal study was conducted in a cohort of ML patients treated at the Laboratory for Leishmaniasis Surveillance of the Evandro Chagas National Institute of Infectious Diseases-Fiocruz, between 2010 and 2013. The patients were submitted to otorhinolaryngologic clinical examination by endoscopy of the upper airways and digestive tract and to speech-language assessment through directed anamnesis, auditory perception, phonation times and vocal acoustic analysis. The variables of interest were epidemiologic (sex and age) and clinic (lesion location, associated symptoms and voice quality. RESULTS: 26 patients under ML treatment and monitored by speech therapists were studied. 21 (81%) were male and five (19%) female, with ages ranging from 15 to 78 years (54.5+15.0 years). The lesions were distributed in the following structures 88.5% nasal, 38.5% oral, 34.6% pharyngeal and 19.2% laryngeal, with some patients presenting lesions in more than one anatomic site. The main complaint was nasal obstruction (73.1%), followed by dysphonia (38.5%), odynophagia (30.8%) and dysphagia (26.9%). 23 patients (84.6%) presented voice quality perturbations. Dysphonia was significantly associated to lesions in the larynx, pharynx and oral cavity. CONCLUSION: We observed that vocal quality perturbations are frequent in patients with mucosal leishmaniasis, even without laryngeal lesions; they are probably associated to disorders of some resonance structures (larynx, pharynx and nasal and oral cavities) or even to compensation mechanisms caused by the presence of lesions in the upper airways and digestive tract.